A study on reproducing silicone shade guide for maxillofacial prostheses matching Indian skin color - Guttal Satyabodh; Patil Narendra; Nadiger Ramesh; Kulkarni Reshma (Wolters Kluwer Medknow Publications, 2008)
Aim: The value and success of a well-fitting and anatomically correct prosthesis are compromised if the color does not match the adjoining tissues. The use of powder colors to help develop a simplified silicone shade guide to aid in the fabrication of silicone facial prostheses for Indian patients has been described here. Materials and Methods: Ten powder pigments were used to fabricate the silicone samples for three different subjects having light, medium and dark complexions who were separated into three groups depending on the value of their shades. Four-step wedge silicone samples with thickness variations of 1, 2, 4 and 6mm were fabricated. Visual assessment of the samples was done by four evaluators to check the agreement of color match. Data was statistically analyzed using kappa coefficients. Results: The kappa values were found to be 0.09-0.44 for a light skin tone, -0.11 to 0.77 for medium skin and 0.44 to 0.85 for dark skin tones. This study showed that the samples of dark skin tone matched the skin tone well and showed a statistically good agreement. To further test the validity of these shade guides, facial silicone veneers were fabricated for three patients having light, medium and dark complexion. The color matching showed satisfactory results. Conclusion: The silicone veneers matched the skin color of all three patients. Hence, this shade guide will help clinicians to obtain a good intrinsic shade and minimize extrinsic coloration.